Rules on Assisted Reproduction on Slovenia – Collision Between Legislation on Biomedically Assisted Procreation and Regulation Relating to Safety and Quality of Tissues and Cells - Vrtačnik, Urban (Medicine, Law & Society, 2019)
Regulatory landscape on assisted reproduction (AR) has changed over the last 20 years in Slovenia. Notwithstanding the fact that in-field legislation (Infertility Treatment and Procedures of Biomedically Assisted Procreation Act – ZZNPOB) has not been amended or derogated since its adoption in 2000, the regulatory framework has been supplemented with legislative acts, implementing EU Directives on safety and quality of tissues and cells used in treatment. Implementation of the latter (also through adoption of Act on Quality and Safety of Human Tissues and Cells for the Purposes of Medical Treatment – ZKVČTC in 2007) has predominantly failed to acknowledge the specifics of assisted reproduction (regulated by ZZNPOB), resulting in regulatory framework which lacks legal certainty and predictability. Article therefore addresses the collision between ZZNPOB and ZKVČTC and proposes solutions de lege ferenda to avoid shortcomings of existing regulation.